Noise levels in the «Hospital Universitario del Valle» newborn intensive care unit «Cirena», Cali, Colombia. (Colombia Medica, 2007)
Introduction:  The high risk newborn babies requires special care and treatment then they have to be move to a exclusive area of the new born intensive care unit (Cirena), where they stay in the hospital during long periods of time and they are more vulnerable to multiple physics and environmental aggressions like noise that can make a negative influence on their clinical situation and post evolution. Objective: Determine level and noise levels in the newborn intensive care unit (Cirena), to planning nurse care to make a contribution to the well being of the new born babies. Methodology:  This is a prospective descriptive study that quantified the sound intensity in different areas of the unit, with a digital sound meter, the study identifies some hours of the day and the noise increment related activities in CIRENA, according to international standards. The statistic analysis was made with SPSS program V 11.5. Results: The study shows that the CIRENA´s noise level is above of the allowed limit, the maximum registered value was 73.6 dB and the minimum value was 46.5 dB, the main source of noise was the people in the room. All the health team needs to keep in mind that is necessary to apply strategies to decrease the noise level  and in this way, reduce the stress level for kids in the hospital.